A comparative study on the environmental impact of supermarket refrigeration systems using low GWP refrigerants. (August 2015) - Beshr, M.; Aute, V.; Sharma, V.; Abdelaziz, O.; Fricke, B.; Radermacher, R.
Abstract: Supermarket refrigeration systems have high environmental impact due to their large refrigerant charge and high leak rates. Consequently, the interest in using low GWP refrigerants such as carbon dioxide (CO2 ) and new refrigerant blends is increasing. In this paper, an open-source Life Cycle Climate Performance (LCCP) framework is presented and used to compare the environmental impact of four supermarket refrigeration systems: a transcritical CO2 booster system, a cascade CO2 /N-40 system, a combined secondary circuit with central DX N-40/L-40 system, and a baseline multiplex direct expansion system utilizing R-404A and N-40. The study is performed for different climates within the USA using EnergyPlus to simulate the systems' hourly performance. Further analyses are presented such as parametric, sensitivity, and uncertainty analyses to study the impact of different system parameters on the LCCP. Highlights: We present a novel framework for the LCCP based design of HVAC&R systems. We analyze the LCCP for supermarket systems with different refrigerants and climates. The transcritical CO2 booster system has the lowest emissions in cold climates. The secondary circuit system offers balance between emissions and energy consumption. Shifting towards low GWP refrigerants decreases the effect of the annual leak rate.